Strategi Komunikasi Korporasi pada Tahapan Perubahan dalam Transformasi Digital di Petronas Aramco - Hidayah, Wulan Rakhmatul; Alifahmi, Hifni (Jurnal Mahardika Adiwidia, 2024)
In line with the advancement of the digital era, Petronas Aramco is committed to building changes in the field of digital technology because transformation changes the way employees communicate and interact during the production and distribution process. The company also has a strategy to achieve its goals and corporate communication plays a role in the company's growth and progress. Researchers use the post positivism paradigm. Researchers used qualitative descriptive methods and purposive sampling technique. Research object at Petronas Aramco. The unit of analysis in this research is the Petronas Aramco department. Data collection methods use interviews and observations as well as literature studies such as references from books, the internet, articles and scientific journals. The aim of this research is to determine the corporate communication strategy and the eight stages of the change concept at Petronas Aramco in optimizing digital transformation efforts and to understand the digital operating model. The results of this research are that behind the digital transformation that has become the company's culture, this is due to the existence of a corporate communication strategy in building change.